EDUCATIONAL VIDEO AS A MEANS OF PREPARING FOR MENOPAUSE: A STUDY ON PREMENOPAUSAL WOMEN AT PKK SWAN GRESIK - Retty Nirmala Santiasari; Shinta Wurdiana Rhomadona; Lina Mahayaty; Nurul Imam (Universitas Nahdlatul Ulama Surabaya, 2025)
Background: Menopause is a natural transition phase characterized by the cessation of the menstrual cycle as well as physical, psychological, and social changes. Many women experience anxiety due to a lack of understanding, which can affect their readiness to face this phase. Readiness to face menopause is a woman's condition to prepare herself to face menopause both physically, mentally and psychologically. Objective: Health education is expected to be able to increase the readiness of premenopausal women to face these changes. Methods: This study used a pre-experimental design with a one group pretest-posttest and cross sectional approach. The number of respondents was 36 premenopausal women who were members of PKK Swan, Menganti Mas, Gresik, selected through purposive sampling techniques. The instrument used was a menopausal readiness questionnaire, and data was analyzed using the Wilcoxon Signed Ranks Test. Result: The results of the statistical test showed a significant difference between the readiness score before and after the health education intervention through educational videos (ρ < 0.001), indicating an increase in women's readiness for menopause after education. Conclusion: Providing health education through educational video media has been shown to be effective in increasing premenopausal women's readiness to face menopause, especially in terms of physical, hormonal, and psychological understanding. This intervention is also able to reduce anxiety and improve negative perceptions of menopause.